1995
DOI: 10.1111/j.1467-8624.1995.tb00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective Influences on Startle in Five-Month-Old Infants: Reactions to Facial Expressions of Emotion

Abstract: Convergent methodologies from studies of fear-potentiated startle in animals and studies of affective modulation of reflex blinks in humans were adapted in order to investigate infants' sensitivity to affective information conveyed by facial expressions of emotion. While 5-month-old infants viewed photographic slides of faces posed in happy, neutral, or angry expressions, a brief acoustic noise burst was presented to elicit the blink component of human startle. Blink size was augmented during the viewing of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…de Haan & Matheson (2009) note that the recognition of emotions relies on both perceptual and conceptual processing as the infant recognizes distinctions in the stimulus characteristics and then extracts meaning. It is likely that all of the infants in the current study can do the former (Balaban, 1995), but it is unclear when the latter emerges. For example, Oakes and Ellis (2013) found that between 4 and 12 months of age, infants can increasingly scan more features of a face, expanding the amount and type of information they could potentially derive.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…de Haan & Matheson (2009) note that the recognition of emotions relies on both perceptual and conceptual processing as the infant recognizes distinctions in the stimulus characteristics and then extracts meaning. It is likely that all of the infants in the current study can do the former (Balaban, 1995), but it is unclear when the latter emerges. For example, Oakes and Ellis (2013) found that between 4 and 12 months of age, infants can increasingly scan more features of a face, expanding the amount and type of information they could potentially derive.…”
Section: Discussionmentioning
confidence: 94%
“…This may be due to infants' neurally-driven “sticky fixation” to attended stimuli (Hood & Atkinson, 1993), working in tandem with a normative bias to preferentially attend to stimulus valence (DeLoache & LoBue, 2009; LoBue & DeLoache, 2010; LoBue et al, 2010). As another example, the presence of an affective face will modulate the early-emerging eye-blink startle by 5 months of age, such that angry faces potentiate the startle response, which is in turn attenuated by happy faces (Balaban, 1995). Perceptual cues may initially capture infants' attention, setting the stage for later conceptual learning regarding the meaning conveyed by emotion faces (Quinn, 2011).…”
Section: Attention To Threat As a Normative Processmentioning
confidence: 99%
“…The ecological approach to social perception, grounded in Gibson's theory of object perception (Gibson, 1979), holds that people's faces provide adaptive information about the social interactions they afford. For example, the 'cute' face of a baby elicits approach and protective responses (Berry & McArthur, 1986;Zebrowitz, 1997); an angry face potentiates avoidance and defensive responses (Balaban, 1995;Marsh, Ambady, & Kleck, 2005). Although ecological theory assumes that our perceptions of faces will often be accurate, it also proposes that attunements to certain facial information can produce biased perceptions through overgeneralization effects (Zebrowitz, 1996(Zebrowitz, , 1997Zebrowitz & Montepare, 2006).…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
“…Interparental conflict may have an impact on early emotional development due to decreases in sensitive caregiving (Krishnakumar & Buehler, 2000), as well as direct exposure to aggressive interactions between caregivers (Crockenberg et al, 2007). Basic research suggests that 5-month-old infants discriminate between different emotional states, with expressions of anger eliciting greater attention and arousal than happy or neutral (Balaban, 1995; Grossmann, Oberecker, Koch, & Friederici, 2010; Grossmann, Striano, & Friederici, 2005). Moore (2009) showed that infants who witnessed vocal anger toward their mother demonstrated altered parasympathetic nervous system responses to an immediately subsequent stressful interaction with their mother.…”
mentioning
confidence: 99%